Analisis Mutu Pelayanan Kesehatan Masyarakat terhadap Kepuasan Pasien di Puskesmas Bukit Lawang Kabupaten Langkat Tahun 2023 - Sari Inrianita; Asriwati Asriwati; Nur Aini (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
The quality of health services is very important to measure how far the Community Health Center is in providing services to patients by looking at the number of BPJS patient visits at the Bukit Lawang Community Health Center, Langkat Regency, which only reached 82.00% in 2020, 77.9% in 2022 and 76.9% in 2023 compared to the target of 95%. Data from the Bukit Lawang Community Health Center, Langkat Regency for the period 2021-2023 showed fluctuations in the number of BPJS patient visits every month. The purpose of this study was to analyze the effect of the quality of public health services on patient satisfaction at the Bukit Lawang Health Center, Langkat Regency in 2023. The research design used a quantitative method with a cross-sectional study approach. The population in this study were all patients who visited the Bukit Lawang Health Center, Langkat Regency in 2023 with an average number of visits of 292 patients per month, the number of samples of 75 people was obtained using a purposive sampling technique. Data analysis used univariate, bivariate and multivariate analysis with logistic regression tests. The results of the study using the chi-square test showed that the variables reliability, assurance, tangible, empathy and responsiveness had a p-value <0.05. The results of the study using the logistic regression test showed that the variables reliability, empathy and responsiveness had a sig. <0.05 and the variables assurance and tangible had a sig.> 0.05. The conclusion of the study is that the variables that significantly affect patient satisfaction are the variables reliability, empathy and responsiveness and the variable that most significantly affects patient satisfaction is the variable reliability.